1974
DOI: 10.1128/aac.6.6.666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of R-Factor-Mediated Genes on Some Surface Properties of Escherichia coli

Abstract: The plasmid RP1 was shown to contain a genetic region (the irp region) responsible for influencing the intrinsic resistance of Escherichia coli to penicillins but not to cephalosporins. Mutants in whic"h the irp genes are inactive were isolated. RP1 carrying functional irp genes protected E. coli AS19 against lysozyme lysis and also enhanced resistance to actinomycin D, to nalidixic acid, and to rifampin. This plasmid also phenotypically repaired the hypersensitivity to penicillins of strain AS19, and also tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1
3

Year Published

1976
1976
1985
1985

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 13 publications
0
16
1
3
Order By: Relevance
“…The fact that it also applies for Ri and RP1 is therefore not surprising. However, there has in the past been some doubt as to whether RP1 carries a locus, specifying intrinsic resistance to penicillins, that is absent from Ri (4). The data presented here (taken together with the results of the accompanying paper [1]) demonstrate that the penicillin resistance phenotype of RP1 can be attributed entirely to the properties of the TEM ,Blactamase.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The fact that it also applies for Ri and RP1 is therefore not surprising. However, there has in the past been some doubt as to whether RP1 carries a locus, specifying intrinsic resistance to penicillins, that is absent from Ri (4). The data presented here (taken together with the results of the accompanying paper [1]) demonstrate that the penicillin resistance phenotype of RP1 can be attributed entirely to the properties of the TEM ,Blactamase.…”
Section: Resultsmentioning
confidence: 62%
“…The calculation assumes that Sp is negligible compared with So (for definition of symbols see appendix). For carbenicillin, this is justified since S, must be less than 4 ,tg/ml, the resistance of R-cells (Table 1). In the case of penicillin G, Sp is probably equal to or less than 1 ,ug/ml, since a mutant of E. coli K-12 with a weakened permeability barrier is susceptible to higher concentrations (2).…”
Section: Resultsmentioning
confidence: 99%
“…Past work has shown that some permeability or antibiotic supersusceptible mutants of P. aeruginosa and E. coli are nonselective and show reduced resistance to a wide range of antibacterial agents (3,(15)(16)(17). Since mutants showing high-level resistance to nalidixic acid and streptomycin can be the result of mutations at the "target" (5, 20), we investigated membrane-bound transpeptidase activity of the carbenicillin-resistant strain and compared it with that of the control in terms of its sensitivity to inhibition by f8-lactam antibiotics.…”
Section: Methodsmentioning
confidence: 99%
“…However Curtis et al (7,8) have reported the isolation of a mutant of RP1, RP1 amp-i, which specifies penicillin resistance in the absence of any detectable f8-lactamase activity. They postulated that RP1 carries a locus, irp, which is responsible for this so-called intrinsic resistance to penicillins.…”
mentioning
confidence: 99%
“…They postulated that RP1 carries a locus, irp, which is responsible for this so-called intrinsic resistance to penicillins. This locus was reported to be absent from Rl, since a point mutant, Rl amp-2, lacked both ,8-lactamase activity and the capacity to determine penicillin resistance (7).…”
mentioning
confidence: 99%